Handbook of Megachurches - Hunt, Stephen (Brill, 2020)
This innovating edited volume provides a broad but detailed overview of a relatively recent significant development in church organisation, the megachurch. Its aim is to capture empirically and theoretically the megachurch phenomenon as a unique form of religious expression through author contributions from several academic disciplines including the Sociology of Religion, Religious Studies, Church History and Theology.